Analysis of the Fight between Islamism and Secularism in the Turkish Elections: Two Dominant Conflicting Forces - Susilowati, Ida; Aulia, Shiva Faizah; Latifah, Aulia Nurul (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
Turkey is the first Islamic country to officially adopt the principle of secularism, a significant change pioneered by Mustafa Kemal Atatürk after the collapse of the Ottoman Empire. The radical implementation of secularism separated religion from state affairs, triggering complex political and social dynamics between Pro-Islam and Pro-Secular groups. In recent decades, particularly under the leadership of Recep Tayyip Erdoğan, Turkey has witnessed a resurgence of Islamic values in politics and public life. Erdogan has succeeded in winning the hearts of the majority of the people through a narrative of Islamic-based national identity, economic development, and a populist approach, which has gradually shifted the dominance of secularism. This study aims to analyse the increasingly intense ideological struggle between Islamism and Secularism and to map contemporary political developments in Turkey. The method used is library research, involving the examination of various relevant academic and media sources. The results of this study offer a deeper understanding of the political and ideological dynamics in Turkey, as well as the impact of the conflict on domestic policies, Turkey's regional position, and the international community's response. Furthermore, this study also reveals how political contestation, mainly through elections, influences the national identity and social order of Turkish society today.Keywords: Secularism; Islamism; Turkish Election; Islamic Revival